Aplikasi Tricoderma sp. dan Streptomyces sp. Terhadap Produksi Bawang Putih (Allium sativum L.) - Dian Utami Zainuddin; Suryani Dewi (JURNAL GALUNG TROPIKA, 2020)
This study aims to determine the effect of Trichoderma sp., And Streptomyces sp., On the production of garlic plants. The research objective was to obtain a combination of biological fertilizers, which are suitable for the cultivation of local Indonesian garlic plants. The study was started by making a suspension by taking the inoculant Trichoderma sp., And Streptomyces sp., Using ose, then put it in a liquid medium and incubated for 5 days. Inoculation of Trichoderma sp., And Streptomyces sp., was done by pouring it into the planting hole area of 5 mL each of the garlic plants according to the treatment consisting of control (without suspension); giving suspension of Trichoderma sp .; Suspense Streptomyces sp .; and Trichoderma sp. + Streptomyces sp. Data were analyzed using the F test, treatments that had a real effect were further tested with the Least Significant Difference Test at the 5% level. The results showed that the treatment significantly affected plant height, dry tuber weight, and tuber diameter. The highest average for all observation parameters was found in the fungus Trichoderma sp. + Streptomyces sp., While the lowest average was in the treatment without the fungal suspension for all parameters of the observation.